Pulmonary artery aneurysm associated with sarcoidosis in a 75-year-old with heart failure: the challenges of diagnosis and management - Isabel Cruz; Rafaela Lopes; Bruno Bragança; Inês Campos; Inês Oliveira; Inês Gonçalves; Rui P. Santos; Aurora Andrade (European Journal of Case Reports in Internal Medicine, 2024)
Introduction: Pulmonary artery aneurysm (PAA) is a rare abnormality of pulmonary vasculature. It can be idiopathic or secondary to various pathologies, frequently with multiple factors leading to its formation. We report the case of a man with concomitant sarcoidosis and PAA. Case description: A 75-year-old male with a diagnosis of pulmonary sarcoidosis was referred to the Cardiology department due to heart failure with reduced left ventricular ejection fraction (LVEF). The transthoracic echocardiogram revealed mildly reduced LVEF, aortic root and pulmonary artery (PA) dilatation, and no signs of pulmonary hypertension (PH). Cardiac magnetic resonance imaging was performed, revealing mild left ventricular dilation, LVEF of 40%, main PA dilation (43 mm) and a pattern of late gadolinium enhancement suggestive of cardiac sarcoidosis. At follow-up, a thoracic computed tomography (CT) angiography scan revealed ascending aorta ectasia and giant main PA aneurysm (60 mm). A right heart catheterisation was performed, and a mean PA pressure of 34 mmHg was obtained. Given the clinical context, the patient was considered to have PH due to lung disease and left heart disease, and PAA was possible due to vascular granulomatous involvement by sarcoidosis. Conclusion: PAA is a rare finding and mostly occurs in the setting of PH. Sarcoidosis is a granulomatous disease that mostly affects the lungs, but the sarcoid involvement of great vessels has been described. In this clinical case, the probable cause for the PA fragility leading to aneurysm formation remains sarcoid vascular infiltration, regarding the discrepancy between the PA dimensions and mildly elevated PA pressure.